PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA KEMENTRIAN TENAGA KERJA DAN TRANSMIGRASI KANTOR JAKARTA SELATAN - Nova Kartikasari; Sri Harini (Fakultas Ekonomi Universitas Djuanda, 2015)
This study aims to determine the effect of Work Stress and Work Environment on Employee Performance Ministry of Labor and Transmigration The City of South Jakarta. Population in this research is the employees Ministry of Labor and Transmigration The City of South Jakarta. Sampling was done by totaling 77 sampling techniques populations. This research is a form of verification. Collecting data through questionnaires and interviews. Test instrument is done with validity and reliability. Analysis of study data include multiple regression analysis, correlation and significance tests simultaneously and partially. Based on the results of multiple regression analysis of job stress and work environment has a positive influence on the performance and results of the F test simultaneously stating that Work Stress and Work Environment influence on employee performance Ministry of Manpower and Transmigration Office of South Jakarta. While the results of the t test stating that the Work Stress and Work Environment partially significant effect on employee performance Labor and Transmigration The City of South Jakarta.Keywords: Job Stress, Work Environment and Employee Performance